Analysis of structure of public debt as a basic stage of information technology - Матвєєва, Юлія Миколаївна (Technology audit and production reserves, 2014)
The structure of public debt as a basic stage of information technology for investigating direct public and publicly guaranteed debt was developed and analyzed in the paper. It includes the following steps: research base formation, econometric models development, analysis of public debt volume changes, depending on internal and external economic factors and forecasting public direct and publicly guaranteed debt volume changes in the near-term outlook. The important role of public debt in the economic life of the country was substantiated in the paper. The role and the influence of the studied object on the state budget balance and consequently on the economy as a whole were pointed out. External direct and publicly guaranteed debt formation sources were revealed, and external public debt effects on the state economy were described. The basic elements of public debt, such as debt type, debt effects, direct and publicly guaranteed debt formation sources were outlined. Direct public and publicly guaranteed debt functioning study, based on the statistical data analysis allows to control peak situations, when the state budget burden, caused by the public debt repayment and servicing is excessive.